Didactic Unit about the Body Parts in Fifth Grade Through CLIL Approach (2023)
This paper presents an intervention proposal of Content and Language Integrated Learning (CLIL) approach in 5th grade of Primary Education in the public school “Rafael Nuñez”, where we are teaching English as a foreign language as preservice teachers. The general aim of this paper is to support students to overcome their language needs and find out how the implementation of the “Human Body Anatomy” didactic unit designed with CLIL could help and develop students in their comprehension skills. Action research methodology is considered and implemented. This research will be on the “Educational Innovation through Multilingualism” research line. A need analysis was diagnosed through class observations and entry tests applied to 25 students. We identified language learning needs, incomprehensible input, low level of reading comprehension skills, and minimal lexical competence. Finally, we do not have too many preliminary advances, we are in the designed strategy step and apply the first activities. Students are motivated with the new proposal tasks.